UMPSA lecturer develops elephant deterrence system using artificial intelligence - Mimi Rabita, Abdul Wahit (UMPSA, 2023)
PEKAN, 15 August 2023 - Lecturer of the Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Ts. Dr. Syafiq Fauzi Kamarulzaman, 37 developed an elephant deterrence system using artificial intelligence to help detect and prevent elephants from intruding livestock farm areas.